ENZALUTAMIDE-INDUCED HEART FAILURE WITH REDUCED EJECTION FRACTION - Todorović Mitić, Mirjana M; Todorović Marković, Marija; Cvetanović, Ana; Čevrljaković, Milan; Dinić, Ljubomir (Acta medicae Medianae, 2026)
Prostate cancer is the second most common malignancy in men and the second leading cause of cancer death. Patients unfit for surgery, with locally advanced or metastatic disease, require androgen-deprivation therapy. In the past decade, enzalutamide and abiraterone were established in prostate cancer treatment. Their safety profile and clinical evidence showed a significant possibility of cardiovascular complications. Heart failure is more common in patients treated with abiraterone. We report a case of a patient with heart failure induced by enzalutamide. In the review of the literature, enzalutmaide-induced heart failure was encountered in only two cases.Further research on the influence of novel anti-androgen therapy on the cardiovascular system, personalized evaluation of the cardiovascular system, and risk stratification for potential cardiovascular adverse events before initiating therapy are needed.
Keywords: enzalutamide, heart failure, prostate cancer